EMC of converters for in terlocking device - Doleček, Radovan; Novák, Jaroslav; Černý, Ondřej (Univerzita Pardubice, 2009)
The paper deals with problems of electromagnetic compatibility (EMC) of frequency control drive of electromotive switch actuator of railway switch. The frequency converter with Pulse Width Modulation (PWM) and the output sinus filter are used for feeding of the asynchronous motor of the switch actuator. This drive is operated in isolated system of feeding voltages. The drive is fed by frequency converter with unshielded cable. The EMC problems occurring at development and operating of drive are analyzed. The new version of contactless safe switch, which works without PWM, is presented at the end of this paper.
Keywords: EMC; interlocking device; electromotive switch actuator